The Role of Parent Education and Parenting Knowledge in Children's Language and Literacy Skills among White, Black, and Latino Families. Issue 2 (25th May 2015) - Rowe, Meredith L.; Denmark, Nicole; Harden, Brenda Jones; Stapleton, Laura M.
Abstract : This study investigated the role of parenting knowledge of infant development in children's subsequent language and pre‐literacy skills among White, Black and Latino families of varying socioeconomic status. Data come from 6, 150 participants in the Early Childhood Longitudinal Study–Birth Cohort. Mothers' knowledge of infant development was measured when children were 9 months old, and child language and pre‐literacy skills were measured during the fall of the preschool year prior to Kindergarten when children were approximately four years old. Mothers' knowledge of infant development was uniquely related to both maternal education and race/ethnicity. Reported sources of parenting information/advice also varied by education and race/ ethnicity and were related to parenting knowledge. Further, controlling for demographic factors, parenting knowledge partially mediated the relation between parent education and child language and pre‐literacy skills, and this relation differed by race/ethnicity. One way to eliminate socioeconomic status achievement gaps in children's early language and literacy skills may be to focus on parents' knowledge of child development, particularly in Latino families. Copyright © 2015 John Wiley & Sons, Ltd.